Nauczyciel edukacji początkowej a uczeń zdolny – wokół problemu (nie)kompetencji - Kwiatkowska-Góralczyk, Małgorzata (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
In my article, I endeavour to outline the reality currently faced by a gifted student in the first to third grades of a public primary school and the daily practices of his or her teacher. I also attempt to reveal the reasons why gifted students rarely receive special attention from the teacher. Many teachers perceive a gifted student as a cause of problems, since such students require that more interest be taken in their persons and that their specific educational needs be met. I also discuss the teacher’s attitudes and actions that make it difficult or even impossible for him or her to conduct proper work and build a proper relationship with a gifted student.